IMPLEMENTASI DAN EVALUASI WEBSITE SMK JAMAAH PASRAH MENGGUNAKAN LARAVEL FILAMENT DENGAN METODE AGILE DEVELOPMENT - Ahmad Miftahul Ulum; Susanto; Atmoko Nugroho (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The advancement of the digital era encourages educational institutions to have informative, functional, and easily accessible websites as a means of delivering information effectively. SMK JAMAAH PASRAH as a technology-based school needs a digital platform to deliver information to students, staff, and the community. This research aims to design and develop the school’s website using the Laravel Filament framework due to its ability to build admin dashboards more quickly, efficiently, and in a structured manner compared to conventional Laravel development, which often requires more time for manually building interfaces and data management logic. The development process adopts the Agile Development method with iterative cycles consisting of plan, design, develop, test, deploy, and review which are carried out repeatedly to achieve optimal results according to user needs. The resulting website has main features such as school information, skill programs, new student registration, articles, and activity galleries. Testing is done using the Black Box Testing method to determine whether all website features function properly. The results of the satisfaction survey using the System Usability Scale (SUS) showed a high level of satisfaction, 85% of 10 respondents. Based on this evaluation, the SMK JAMAAH PASRAH website has succeeded in becoming an effective digitization solution, presenting structured, easily accessible information, and increasing the efficiency of school administration.